Rule-based tools for the configuration of ambient intelligence systems: a comparative user study - Cabitza, Federico; Fogli, Daniela; Lanzilotti, Rosa; Piccinno, Antonio (Multimedia tools and applications, 2017)
This paper describes a 63-participant user study that compares two widely known systems supporting end users in creating trigger-action rules for the Internet of Things and Ambient Intelligence scenarios. The user study is the first stage of a research agenda that concerns the implementation of a novel conceptual framework for the design and continuous evolution of ‘sentient multimedia systems’, namely socio-technical systems, where people and many kinds of hardware/software components (sensors, robots, smart devices, web services, etc.) interact with one another through the exchange of multimedia information, to give rise to intelligent, proactive behaviors. The conceptual framework is structured along three layers - physical, inference and user – and is based on an information space of events, conditions and actions, linked together in Event-Condition-Action rules and operating according to the interconnection metaphor. The results of the user study have provided some indications for the implementation of the user layer, suggesting which could be the most suitable interaction style for rule design by a community of end users (e.g. a family) and which issues should be addressed in such a wide context.